Scott Pilgrim vs. The World [videorecording (DVD)] - Wright, Edgar, 1974-; Wright, Edgar, 1974-; Wright, Edgar, 1974-; Cera, Michael; Winstead, Mary Elizabeth; Culkin, Kieran; Evans, Chris, 1981-; Kendrick, Anna; Larson, Brie, 1989- (Universal Studios Home Entertainment, 2010)
Meet charming and jobless Scott Pilgrim. A bass guitarist for garage band Sex Bob-omb, the 22-year-old has just met the girl of his dreams, literally. The only catch to winning Ramona Flowers? Her seven evil exes are coming to kill him. As Scott gets closer to Ramona, he must face an increasingly vicious rogues' gallery from her past, from infamous skateboarders to vegan rock stars and fearsome identical twins. If he hopes to win his true love, he must vanquish them all.